Moderating roles of national culture for alliance relationship advantages and performance in Asia. Issue 3 (3rd July 2018) - Kang, Seongho; Im, Subin; Park, Heungsoo
ABSTRACT: Purpose: Despite the fact that some studies examine the role of cultural attributes as determinants of successful alliance relationships, there has been lack of studies that explored how a firm's orientation toward alliances, as a culture, might provide competitive advantages in the form of alliance relationship, which influences the firm's performance. The current study therefore proposes a research model, in which alliance orientation as an intangible resource enhances the alliance relationship advantage, which eventually improves alliance performance, with national culture as a moderator. Design/methodology/approach: To test the hypotheses, responses were obtained from 145 South Korean and 123 Chinese firm samples. The proposed model was estimated using structural equation modeling and hierarchical regression analysis. Findings: The empirical study confirms that alliance orientation directly influences alliance relationship advantage, en route to alliance performance. When uncertainty avoidance is greater, the relationship between alliance relationship advantage and alliance performance grows weaker, whereas when masculinity and long-term orientation are greater, this relationship becomes enhanced. Research implications: Leveraging source–positional advantage–performance structures (Day and Wensley 1988), this study clarifies how alliance orientation influences a firm's alliance relationship advantage as a positional advantage, which eventually enhances its alliance performance. Moderating effects of cultural factors arise between alliance orientation and alliance relationship advantage, thereby revealing the important, contingent role of cultural factors in managing the link between alliance orientations and competitive advantage. Practical implications: This study provides managerial guidelines for how firms operating in different countries such as Korea and China can manage their alliance orientation and alliance-related activities to enhance their competitive advantages and firm performance, by noting and accommodating different cultural characteristics. Originality/value/contribution : The proposed contingency model relies on the moderating role of national culture, reflected by uncertainty avoidance, masculinity, and long-term orientation, to explain the relationships between alliance competitive advantages and alliance performance.